Real meaning of Togay Murad's novel "Fields left by my father" - Kenjayeva Munira (Proceedings of The ICECRS, 2020)
Togay Murad's heroes fit the spirit of the time, especially the worldview of independent youth. Our national traditions and nationality are very bright in it. It is for this reason that the writer realizes the problem before his contemporaries. Togay Murad encourages them to do the same. In his novel “The Fields Left by My Father”, three members of an Uzbek peasant dynasty - grandfather, father and son - represent the fate of the Uzbek people's 130 years of oppression. His life is revealed with artistic skill. In this article I am on the verse to describe this historical period in details.